Finite element analysis of rectangular composite plates subjected to a uniformly distributed load - Hng, Stantly Jian Zong (Nanyang Technological University, 2022)
Most structures are subjected to severe static and dynamic stress, as well as a variety of constrained situations, during their service lives. As a result, the structure may flex, buckle, or vibrate. Precise forecasting of the static and vibration responses of laminated composite /skew plates with low computational cost and high precision is critical. ANSYS Workbench is used to develop an appropriate finite element model based on first order shear deformation theory. This project provides a thorough investigation into the responses of rectangular composite plates subjected to a uniformly distributed load. Under different simply supported conditions, finite element modeling (FEM) was used to predict the response of a rectangular composite plate made up of a layer of resin epoxy sandwiched between two thin layers of carbon fibers. A convergence analysis was also performed to establish the best mesh size for the FEM analysis. The simulation was conducted under static structural analysis with an anti-symmetric and symmetric laminate plate under four different simply supported conditions. The maximum Y-deflection of the rectangular plates is then recorded accordingly. These responses are then further compared with the exact and approximate theoretical solutions. Parametric effects (support conditions, ply orientations, numbers of layers, thickness ratio) are also discussed in detail.